Análise transiente das principais variáveis na perfuração de poços de petróleo durante a ocorrência do Kick - Oliveira, Francisco Freire de (2014)
Oil exploration over the decades has become increasingly difficult as the available reserves or are increasingly scarce or are located in regions of difficult access and depths increasing and therefore, subjected to high pressures and temperatures. The drilling of petroleum wells demand large investments and highly skilled personnel for the operation to be economically viable. The knowledge of the available technologies and the choice of appropriate materials are important factors in this area. In extreme situations drilling requires strict process control. For this reason, one of the most important points in the drilling process is controlling the pressure within the well. If this control fails, the influx of formation fluids into the well can occur featuring a kick. It is essential a greater understanding of this phenomenon. Aiming at this goal, this study addresses the fundamentals of drilling, types of drilling fluids and the mechanisms, causes and signs of kicks, as well as the main methods of well control that have been utilized. The study also includes the major patterns of upward two-phase flow, as well as a summary of the kick simulators ever developed. To deepen this knowledge, a simplified simulator kick in ANSYS® CFX software is developed to analyze the behavior of some variables inside the pit during the occurrence of a gas kick. In this model, it is evaluated the behavior of dynamic variables such as pressure, viscosity, volumetric fractions and densities of fluids inside the tube during drilling. Also comparisons are made with different fluids with different rheological behavior and three turbulence models. For the variable pressure, it is observed that the behavior is similar to a conventional leak in a pipe. The behaviors of some Power Law fluids and Bingham fluids are analyzed. It noted that the gas spreads more quickly when the drilling fluid has rheological behavior of Bingham plastic. Among the turbulence models analyzed (k-ε, RNG- k-ε e SST), it is observed that the SST is the turbulence model which provides a more rapid decrease in the concentration of drilling fluid at the analyzed points. This model also allows a greater pressure drop along the stretch of the well examined in the final moment of the simulation.